Clinical Applications Measuring Arterial Stiffness: An Expert Consensus for the Application of Cardio-Ankle Vascular Index. (16th November 2021) - Budoff, Matthew J; Alpert, Bruce; Chirinos, Julio A; Fernhall, Bo; Hamburg, Naomi; Kario, Kazuomi; Kullo, Iftikhar; Matsushita, Kunihiro; Miyoshi, Toru; Tanaka, Hirofumi; Townsend, Ray; Valensi, Paul
Abstract: BACKGROUND: The purpose of this document is to provide clinicians with guidance, using expert consensus, to help summarize evidence and offer practical recommendations. METHODS: Expert Consensus Documents are intended to provide guidance for clinicians in areas in which there are no clinical practice guidelines, especially for new and evolving tests such as arterial stiffness measurements, until any formal guidelines are released. RESULTS: This expert consensus document is intended as a source of information for decision-making and to guide clinician–patient discussions in various clinical scenarios. CONCLUSIONS: The goal is to help clinicians and patients make a more informed decision together. Graphical Abstract: